Vehicle Loading System on KMP. PORT LINK III for Sea Transportation Safety - Chairul Insani Ilham; Santy Katharina; Desi Yanti (Politeknik Transportasi Sungai, Danau dan Penyeberangan Palembang, 2023)
Loading is a process of loading by transferring cargo from land to ships that are carried or transported to the destination safely which is carried out according to procedures at the port by ship crews and land parties with existing loading and unloading tools, either from the ship itself or from land. This qualitative research is a descriptive approach. The data analysis used is a qualitative approach to primary data through interviews, observations, documentation and secondary data in the study of legislation, books or literature related to the vehicle loading system on board. It can be concluded about the vehicle loading system for marine transportation safety. In the implementation of transportation services, loading constraints are still found, such as vehicle loading procedures that are still not in accordance with existing regulations. This results in the process of regulating vehicle loads on the loading deck only based on feeling and the absence of lashing for securing vehicle loads.